Gestión financiera del capital de trabajo en las empresas del sector tecnológico - Murillo González, Edwin Marcos (2024)
The financial management of working capital is of vital importance for the commercial computer technology sector, since it allows it to have the necessary liquidity to meet its financial obligations and maintain its solvency in the long term. The objective of this research is to determine how financial management influences the working capital of companies in the commercial computer technology sector. The problem is that many companies, especially SMEs, show high rates of insolvency, which can lead to the closure of their establishments. In this context, it is essential that companies use financial tools to make informed decisions and avoid liquidity problems. The mixed methodology to be applied in this research combines both quantitative and qualitative methods to approach the social reality of companies in the IT business technology sector. The study foresees the identification of strengths and weaknesses in the financial management of working capital in these companies, and proposes solutions to improve their financial solvency and avoid insolvency problems. This research is expected to contribute to the development of a stronger and more profitable commercial computer technology sector.